Political realism and the fantastic romantic German liberal discourse and the Sámi in Theodor Mügge’s novel Afraja (1854) - Theodorsen, Cathrine (Nordlit, 2008)
The novel Afraja, written by the German author and liberal Theodor Mügge and published in 1854 provides an opportunity to explore connections between travel writing and adventure stories from the perspective of one of Germany's most popular writers of the nineteenth century. The focus of my discussion in this paper is to explore the implications of the meeting between a fictional Sámi, living in the exotic North and a Danish aristocratic adventurer whose attitudes reflect the discourse of Mügge's politically liberal views. Additionally, Mügges fiction sketches out different images of the Sámi.